Letters and Stars: A New Wordplay in the Aratea (fr. 34 Soubiran, vv. 1-6) - Crotto, Alberto (Ciceroniana On Line, 2021)
This paper investigates a possible telestich in Cicero’s Aratea that has so far escaped the notice of scholars. The article’s objective is to develop our understanding of the phenomenon of technopaegnia in Cicero’s poetic corpus, analysing the style, context, and literary intent at work in this specific lusus.